Pelatihan Mengelola Impostor Phenomenon pada Orang Muda Afiliasi Kolektif Menjadi Manusia - Princen; Theresia, Allessandra; Sugianto, Dicky; Sinaga, Nurtaty; Ismau, Phutri A. G.; Oktafiani, Rhema; Chandrakusuma, Wynne D. (Devotion : Jurnal Pengabdian Psikologi, 2023)
Impostor phenomenon is one of mental health issues which poses risk for an individual, especially in youths. Management of impostor phenomenon within youth is urgent to maintain their mental health. The problem of impostor phenomenon also found in Menjadi Manusia collective affiliated, in which the youth affiliated with this collective was identified experiencing impostor phenomenon. We conducted serial activities within a workshop to help these youth in managing impostor phenomenon. The workshop designed as psychoeducation and psychological intervention to equip the youth in understanding and managing impostor phenomenon. Participants’s feedback about the workshop suggests that it helped them to understand and manage impostor phenomenon. Results of this workshop serve as an initial suggestion on how to manage impostor phenomenon, particularly in Menjadi Manusia collective affiliated.